Motion - Pancreatic Endoscopy is Useful for the Pain of Chronic Pancreatitis: Arguments for the Motion - Stanley M Branch (Canadian Journal of Gastroenterology)
Pain is the dominant clinical problem in patients with chronic pancreatitis. It can be due to pseudocysts, as well as strictures and stones in the pancreatic ducts. Most experts agree that obstruction could cause increased pressure within the main pancreatic duct or its branches, resulting in pain. Endoscopic therapy aims to alleviate pain by reducing the pressure within the ductal system and draining pseudocysts. Approaches vary according to the specific nature of the problem, and include transgastric, transduodenal and transpapillary stenting and drainage. Additional techniques for the removal of stones from the pancreatic duct include extracorporeal shockwave lithotripsy. Success rates for stone extraction and stenting of strictures are high in specialized centres that employ experienced endoscopists, but pain often recurs during long term follow-up. Complications include pancreatitis, bleeding, infection and perforation. In the case of pancreatic pseudocysts, percutaneous or even surgical drainage should be considered if septae or large amounts of debris are present within the lesion. This article describes the techniques, indications and results of endoscopic therapy of pancreatic lesions.